Management of tracheostomy in COVID-19 patients: The Japanese experience. Issue 3 (June 2021) - Yokokawa, Taizo; Ariizumi, Yosuke; Hiramatsu, Mariko; Kato, Yujin; Endo, Kazuhira; Obata, Kazufumi; Kawashima, Kayoko; Sakata, Toshifumi; Hirano, Shigeru; Nakashima, Torahiko; Sekine, Tatsurou; Kiyuna, Asanori; et al.
Abstract: Objective: Involvement in the tracheostomy procedure for COVID-19 patients can lead to a feeling of fear in medical staff. To address concerns over infection, we gathered and analyzed experiences with tracheostomy in the COVID-19 patient population from all over Japan. Methods: The data for health-care workers involved in tracheostomies for COVID-19-infected patients were gathered from academic medical centers or their affiliated hospitals from all over Japan. Results: Tracheostomies have been performed in 35 COVID-19 patients with a total of 91 surgeons, 49 anesthesiologists, and 49 surgical staff members involved. Twenty-eight (80%) patients underwent surgery more than 22 days after the development of COVID-19-related symptoms (11: 22–28 days and 17: ≥29 days). Thirty (85.7%) patients underwent surgery ≥ 15 days after intubation (14: 15–21 days, 6: 22–28 days, and 10: ≥29 days). Among the total of 189 health-care workers involved in the tracheostomy procedures, 25 used a powered air-purifying respirator (PAPR) and 164 used a N95 mask and eye protection. As a result, no transmission to staff occurred during the 2 weeks of follow-up after surgery. Conclusion: No one involved in tracheostomy procedures were found to have been infected with COVID-19 in this Japanese study. The reason is thought to be that the timing of the surgery was quite late after the infections, and the surgery was performed using appropriate PPE and surgical procedure. The indications for and timing of tracheostomy for severe COVID-19 patients should be decided through multidisciplinary discussion.